miR-21 Protects Against Ischemia/Reperfusion-Induced Acute Kidney Injury by Preventing Epithelial Cell Apoptosis and Inhibiting Dendritic Cell Maturation - Song, Nana; Zhang, Ting; Xu, XiaLian; Lu, Zhihui; Yu, Xiaofang; Fang, Yi; Hu, Jiachang; Jia, Ping; Teng, Jie; Ding, Xiaoqiang (Frontiers in Physiology, 2018)
Renal tubular injury and innate immune responses induced by hypoxia contribute to acute kidney injury. Accumulating evidence suggests that miR-21 overexpression protects against kidney ischemia injury. Additionally, miR-21 emerges as a key inhibitor in dendritic cell maturation. Thus, we hypothesized that miR-21 protects the kidney from IR injury by suppressing epithelial cell damage and inflammatory reaction. In this study, we investigated effects of miR-21 and its signaling pathways (PTEN/AKT/mTOR/HIF, PDCD4/NFκ-B) on kidney ischemia/reperfusion (IR) injury in vitro and in vivo. The results revealed that IR increased miR-21, HIF1α and 2α expression in vivo and in vitro. MiR-21 interacted with HIF1α and 2α through the PTEN/AKT/mTOR pathway. Moreover, inhibition of miR-21 activated PDCD4/NFκ-B pathways, which are critical for dendritic cell maturation. Renal IR triggers local inflammation by inducing the dendritic cell maturation and promoting the secretion of IL-12, IL-6 and TNF-α cytokines. Knockdown of miR-21 intensified the effect of IR on tubular epithelial cell apoptosis and dendritic cell maturation. Our results suggested that IR-inducible miR-21 protects epithelial cells from IR injury via a feedback interaction with HIF (PTEN/AKT/mTOR/HIF/miR-21) and by inhibiting maturation of DCs through the PDCD4/NF-κB pathway. These findings highlight new therapeutic opportunities in AKI.